Comparative Study: Values Of Character Education In The Book Of Ayyuhal Walad By Imam Al Ghazali And The Great Personal Book By Buya Hamka - Nizar, Abdul (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
This research aims to 1) Describe the concept of Character Education Values in the book Ayyuhal Walad by Imam Al Ghazali and the book Pribadi Hebat by Buya Hamka 2) Describe and analyze the similarities and differences in Character Education Values in the book Ayyuhal Walad by Imam Al Ghazali and the book Pribadi Hebat by Buya Hamka.  For these reasons, the researcher attempted to find out the values of character education in the book Ayyuhal Walad by Imam Al Ghazali and the book Pribadi Hebat by Buya Hamka, then compared the principles, objectives, and methods used in character education. The method in this research uses library research methods, namely research whose data sources are obtained through library studies or related literature. This research is descriptive comparative analytical, namely explaining, explaining analyzing, and comparing thoughts systematically, so it is easy to understand and conclude and then analyze regarding the similarities and differences in thinking in character education. The results of the research state that the character education values offered by Imam Ghazali and Buya Hamka have quite significant differences, both in terms of principles, objectives, and educational methods presented.  This is influenced by differences in socio-cultural backgrounds and quite large differences in life span. However, there are substantial similarities between the two figures from a religious perspective.   Keywords: Character building, Ayyuhal walad, Imam Al Ghazali, great personality, Buya Hamka